Real Time Face Recognition System (RTFRS) - Haji, Suad; Varol, Asaf (Ieee, 2016)
Biometrics is a term used to define an individual's DNA, hand geometry, face, etc. or behavioral characteristics, such as hand signature, voice tone, keystrokes and so on. For that reason, these biological characteristics are unique for every individual. In many situations, face recognition related technologies are becoming more popular among biometric-based technologies that measure an individual's natural data. Genetic biometrics has generally used to authenticate and identify individuals by analyzing their physical characteristics, such as fingerprint, eye iris, vein etc. Instead of using a bankcard, a camera installed at the Automated Teller Machines would capture pictures of faces of customers, and compare them with the photos of account holders in the database of banks to verify the customer's identity. The purpose of this paper is to present a Windows based real time application system using face recognition algorithms. This new system can be applied in various different fields such as identity verification and other potential commercial applications. Both Eigen and Local Binary Patterns face algorithms were used to reduce the impact of light exposure that will affect the accuracy of the system.
4th International Symposium on Digital Forensic and Security (ISDFS) -- APR 25-27, 2016 -- Little Rock, AR
Keywords: Face Detection; Face Recognition; Eigen Faces; LBP algorithms